Case report: paraneoplastic cerebellar degeneration associated with anti-Yo antibody successfully treated with ofatumumab - Jingjing Dou; Xiaotong Yue; Haitao Ren; Chunjuan Wang; Shougang Guo; Shougang Guo (Frontiers in Immunology)
Paraneoplastic cerebellar degeneration (PCD) with anti-Yo antibodies represents a rare immune-mediated paraneoplastic neurological syndrome. Its diagnosis and management remain clinically challenging. Here, we present a case of PCD with confirmed anti-Yo antibodies, validated through anti-cerebellar degeneration protein 2 (CDR2) and anti-CDR2-like antibodies detection, which demonstrated a favorable response to ofatumumab therapy. The patient initially manifested with dizziness, nystagmus, dysarthria, and ataxia. Initial testing revealed weakly positive anti-Yo antibodies, accompanied by positive serum tissue-based assay result for cerebellum. Following one course of intravenous immunoglobulin and methylprednisolone pulse therapy, improvement of the patient’s dizziness was observed. Oral prednisone was prescribed for maintenance therapy. However, after discharge, the patient experienced progressive deterioration of symptoms, including worsening dizziness, dysarthria, and limb ataxia. Upon readmission to our hospital, further immunological testing confirmed the presence of anti-CDR2 and anti-CDR2-like antibodies. When a second course of methylprednisolone pulse therapy proved ineffective, treatment was switched to ofatumumab. After two doses, the patient achieved partial symptomatic relief.